2014
DOI: 10.1007/s00277-014-2190-1
|View full text |Cite
|
Sign up to set email alerts
|

Early CMV replication and subsequent chronic GVHD have a significant anti-leukemic effect after allogeneic HSCT in acute myeloid leukemia

Abstract: Early cytomegalovirus (CMV) replication (eCMV) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) has been suggested as an independent factor that reduces leukemia relapse risk. We retrospectively analyzed 74 patients with acute myeloid leukemia (AML) who underwent allo-HSCT between August 2006 and September 2012. All recipients were CMV seropositive. In 52 patients, eCMV occurred at a median of 35 days (range, 11-92) after allo-HSCT. Univariate analysis revealed that the factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 25 publications
3
44
1
1
Order By: Relevance
“…Thus, these factors may reduce the protective effect of CMV reactivation from relapse in the cohort of the Seattle group. Nevertheless, another recent retrospective analysis involving adult patients with AML from South Korea [19] and from St. Louis Figure 2. Cumulative incidence of relapse (CIR) stratified by post-transplantation CMV reactivation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, these factors may reduce the protective effect of CMV reactivation from relapse in the cohort of the Seattle group. Nevertheless, another recent retrospective analysis involving adult patients with AML from South Korea [19] and from St. Louis Figure 2. Cumulative incidence of relapse (CIR) stratified by post-transplantation CMV reactivation.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, in a large cohort of patients, Green et al found only a modest protective effect of CMV reactivation on relapse in patients with AML after allo-HSCT without any benefit in OS because of increased nonrelapse mortality (NRM) [17]. Several groups have suggested a similar association in a cohort of patients with AML or chronic myeloid leukemia (CML) [18,19]. In contrast, a protective effect of CMV reactivation on reducing relapse is not evident in patients with acute lymphoblastic leukemia (ALL) [17], lymphoma [17,20], myelodysplastic syndrome (MDS) [7], and pediatric acute leukemia [21].…”
Section: Introductionmentioning
confidence: 95%
“…1,4 In contrast, Jang et al as well as our group found that, in single-center studies, CMV reactivation was associated with an improved OS rate. 9 Green et al observed a reduced risk of relapse by day 100 among patients with AML after transplant, but not in patients with ALL, lymphoma, CML, and MDS, whereas at 1 year after transplant CMV reactivation was associated with reduced risk of relapse in all patients but without achieving statistical significance. 3 The Japanese register study of Takenaka et al reported a reduced risk of relapse after CMV reactivation only in AML, but not in ALL, lymphoma, or MDS.…”
mentioning
confidence: 99%
“…1 In contrast, we and others have published that CMV reactivation correlates with substantially improved reduction of relapse incidence in patients with AML after transplant. [2][3][4][5][6][7][8][9][10] The antileukemic effect of CMV reactivation is pronounced in AML and chronic myeloid leukemia (CML), but is detectable to a lesser extent in myelodysplastic syndrome (MDS), acute lymphoblastic leukemia (ALL), non-Hodgkin lymphoma, and pediatric acute leukemia. [3][4][5][6][7][8][9][10] We defined this remarkable phenomenon as a virus-versus-leukemia effect, which is rare in hematology and contrary to the effects of oncovirus causing cancer or hematological malignancies such as hepatitis B and C virus, Epstein-Barr virus, human T-lymphotropic virus, Kaposi sarcoma-associated herpes virus, and human papilloma virus.…”
mentioning
confidence: 99%
“…Some single-center studies have noted an unexpected association of positive CMV serology or early (before 100 days after HCT [D100]) CMV reactivation with decreased incidence of hematologic disease relapse following allogeneic HCT. [8][9][10][11][12][13] Although initially described in preventing acute myelogenous leukemia (AML) relapse, this putative protective effect of CMV reactivation Age at transplant, years ,.001 #10 157 (5) 97 (9) 145 (6) 209 (8) 11-20 362 (11) 139 (13) 212 (8) 262 (10) 21-30 408 (13) 125 (12) 288 (11) 336 (13) 31-40 493 (15) 135 (13) 317 (12) 339 (13) 41-50 618 (19) 187 (17) 529 (20) 515 (20) 51-60 779 (24) 262 (24) 674 (26) 570 (22) .60 436 (13) 129 (12) 442 (17) 304 (12 African American 192 (6) 50 (5) 91 (3) 52 (2) Asian/Pacific Islander 381 (12) 42 (4) 65 (2) 27 (1) Hispanic 450 (14) 106 (10) 236 (9) 154 (6) Other 321 (10) 40 (4) 55 (2) has also been observed against chronic myeloid leukemia (CM...…”
Section: Introductionmentioning
confidence: 99%